GIRAFFOKERYX (ARTIODACTYLA: RUMINANTIA: GIRAFFIDAE) FROM THE POTWAR PLATEAU MIDDLE MIOCENE, PAKISTAN - K. Aftab; Z. Ahmed; M. A. Khan; M. Akhtar (Journal of Animal and Plant Sciences, 2014)
Giraffokeryx remains are described from Chinji Formation of Lower Siwaliks. The material referred to this species comprises mandible fragments and isolated teeth. The studied specimens have been compared with the relevant specimens in the Geological Survey of India, American Museum of Natural History (AMNH) and Punjab University Paleontological Collection Stored in Zoology Department (Pakistan). The lower cheek teeth are quadrate with a very weak stylids, median ribs and ectosytlids. In most of the specimens, there is a trend towards the heightening of the crown from the lower Chinji to the upper Chinji Formation.
Keywords: Giraffids; Giraffokerycinae; Chinji Formation; Lower Siwaliks